PENERAPAN MODEL WATERFALL DALAM PERANCANGAN APLIKASI DIGITAL CUSTOMER RELATIONSHIP MANAGEMENT PRODUK FASHION - Harjunawati, Sri; Baidawi, Taufik; Hendarsih, Ida (INTI Nusa Mandiri, 2024)
To win business competition and maintain market share, companies are required to be able to adapt to market conditions and use appropriate marketing strategies. Customer Relationship Management (CRM) is a marketing strategy to create and maintain good relationships with customers thereby reducing the possibility of customers moving to competitors. The aim of the research is to analyze and develop web-based CRM in the Marketing Information System at Toko Agung, East Jakarta. The research method used in this research is the Software Development Method using the waterfall model. The result is a web-based CRM system application that can manage customer data, product orders, payments and delivery of goods to customers. The implementation of this web-based digital CRM application is expected to make it easier for customers to select the desired product, place an order, make payments and receive goods without having to come to Toko Agung. For busy customers, this system is more efficient and effective. It is hoped that this convenience will have an impact on repeat purchases and will increase sales volume, which can then increase company profits. The Customer Relationship Management (CRM) application can simplify, speed up and optimize the quality of customer service, especially at Toko Agung, East Jakarta.